International Marketing Adaptation Strategies of Riau Sago Noodles to Meet Taiwanese Consumer Preferences: Analysis of Smes in Riau Province - Lita Arfah (Universitas Negeri Makassar, 2026)
This study aims to examine the international marketing adaptation strategies adopted by Riau sago noodle SMEs to meet Taiwanese consumer preferences and identify the challenges encountered during market expansion. A qualitative multiple case study approach was employed to gain an in-depth understanding of SMEs' adaptation practices. Data were collected through semi-structured interviews, observations, and document analysis involving ten participants, including SME owners, a production manager, an export consultant, a government representative, and an SME development officer in Riau Province, Indonesia. First, SMEs adapted their products to align with Taiwanese consumer preferences by improving product quality, modifying flavor and texture where appropriate, and ensuring compliance with food safety and quality standards required for export markets. Second, packaging and labeling were redesigned by incorporating vacuum-sealed packaging and bilingual information to enhance product attractiveness and consumer trust. Third, SMEs adopted cultural branding strategies by positioning Riau sago noodles as authentic traditional Malay food products with distinctive cultural heritage. Fourth, digital marketing platforms were utilized to promote products internationally and establish direct interactions with potential consumers. Finally, several challenges were identified, including limited market intelligence, certification requirements, and inadequate export networks.The study concludes that successful internationalization requires an integrated adaptation process combining product innovation, cultural authenticity, digital marketing capabilities, and institutional support. These findings provide theoretical contributions to the SME internationalization literature and practical implications for developing export-oriented strategies for traditional food products in emerging economies.